Spatial and socioeconomic patterns of COVID-19 in transition zones between municipalities in eastern Amazonia - Dinar Duarte Vasconcelos; Dinar Duarte Vasconcelos; Dinar Duarte Vasconcelos; Dinar Duarte Vasconcelos; Hermes Fonsêca de Medeiros; Hermes Fonsêca de Medeiros; Hermes Fonsêca de Medeiros; José Antonio Herrera; José Antonio Herrera; José Antonio Herrera; Lucas de Oliveira Lima; Lucas de Oliveira Lima; et al. (Frontiers in Public Health)
BackgroundHerein, we assess hospitalizations and deaths from COVID-19 in Amazonian municipalities, taking into account regional, demographic, and socioeconomic peculiarities. Public data from 2020 and 2021 of 52,082 cases of COVID-19 were analyzed in R Program.MethodsWe examined the interaction of mortality, hospitalization, and fatality rates of COVID-19, considering socioeconomic, demographic, and geographic variables. We measured the spatial autocorrelation of the rates associated with the variables POP, GDP, Residents, HDI, and GINI. The spatial patterns found show distinctly affected sectors and COVID-19 transition zones between municipalities.ResultsWe detected higher mortality rates in territories with greater social and environmental vulnerability. Analysis of the mortality rate indicates that all the socioeconomic variables tested are associated with this variable, but their effects interact in a complex way. The municipalities with higher numbers of residents per household and Gini coefficients had higher fatality rates, and municipalities with a higher GDP were more associated with higher hospitalization and mortality rates. Furthermore, the five socioeconomic indices included in multiple regressions analyzing mortality and hospitalization rates exhibited significant interaction effects. However, no significant interaction effects were observed in the fatality rate analyses.ConclusionSpatial analyses showed that none of the 144 municipalities studied had high overlapping rates of mortality, hospitalization, and fatality rates for COVID-19 in the same municipality. We recommend further studies in the transition zones, considering the municipalities of Floresta do Araguaia, Mãe do Rio, and Redenção for mortality, Barcarena, Capitão Poço, and Redenção for hospitalization, and Cumaru do Norte and Pau D’Arco for fatality, in order to understand the health dynamics of each territory. The most affected areas are located near the border with the state of Amazonas. We recommend the adoption of personalized strategies for Amazonian municipalities when targeting future public health events.